The Influence Of Service Quality On Customer Satisfaction At Bank Bengkulu Main Branch - Setyaningsih, Endang; Saputra, Harius Eko; Maryaningsih, Maryaningsih (Social Sciences Journal, 2025)
This study aims to determine the influence of service quality on customer satisfaction at Bank Bengkulu Main Branch. The research employed a descriptive associative method, with data collected through questionnaires and documentation. The data were analyzed using simple linear regression to test the relationship between service quality (X) and customer satisfaction (Y). The sample consisted of 85 respondents who were customers of Bank Bengkulu Main Branch. The findings indicate a strong correlation between service quality and customer satisfaction, with an R value of 0.744 or 74.4%. The t-test results confirmed that service quality has a significant effect on customer satisfaction. Therefore, improving service quality is a crucial factor in enhancing customer satisfaction at Bank Bengkulu.